2009
DOI: 10.1002/pola.23387
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated polyelectrolyte with pendant carboxylate groups: Synthesis, photophysics, and pH responses in the presence of surfactants

Abstract: This article reports the synthesis, optical properties, and pH responses of a water-soluble poly(phenylene ethynylene) with pendant carboxylate groups. This conjugated polyelectrolyte, PPE-OBS, was prepared via a facile synthetic route, using 1,4-di(ethyl 4-oxy-butyrate)-2,5-diiodo-benzene as polymeric monomer and followed by the alkali induced saponification. PPE-OBS absorbs strongly in the blue region and emits a moderately intense fluorescence. However, it subjects to unstable emission in neutral aqueous me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 70 publications
0
20
1
Order By: Relevance
“…The title compound was synthesized according to the method of Zhang et al 2009. To a solution of p-dihydroxybenzene (0.01 mol) in acetonitrile (50 ml), anhydrous potassium carbonate (0.02 mol) and ethyl 4-bromobutanoate (0.01 mol) were mixed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The title compound was synthesized according to the method of Zhang et al 2009. To a solution of p-dihydroxybenzene (0.01 mol) in acetonitrile (50 ml), anhydrous potassium carbonate (0.02 mol) and ethyl 4-bromobutanoate (0.01 mol) were mixed.…”
Section: Methodsmentioning
confidence: 99%
“…For related structures of multidentate O-donor ligands such as benzene-1,4-dioxydiacetic acid and benzene-1,4-dioxydibutanoic acid, see: Dai et al (2009);Zhu et al (2008); ; Yang et al (2010); Zhao (2011). For the synthesis of the title compound, see: Zhang et al (2009). For standard bond lengths, see: Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 98%
“…22 Unlike that of their small molecule counterparts, the unique π-π* conjugated electronic structure of CPs allows for rapid transfer of excitation along the entire backbone to energy/electron receptors, thereby resulting in a remarkable amplification of optical response. 23 Studies that detect metal ions with CPs in organic solvents have been proposed in the past 10 years. [24][25][26] However, toxic heavy metal ions mainly exist in aqueous solutions, and the quenching process of CPs and metal ions in aqueous solutions is rarely studied.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Fan et al reported the synthetic route, optical properties, pH responses, and subsequent studies on the interaction and stabilization of poly(2,5-bis(sodium 4-oxybutyrate)-1,4-phenylethynylene-alt-1,4-phenyleneethynylene (PPE-OBS) with various surfactants. 23 Pei et al investigated an antioxidant probe based on a bimodal PPE-OBS-SO3. 31 A highselectivity and high-sensitivity fluorescent sensor for detecting highly toxic Hg 2+ was developed using PPE-OBS because of the good water solubility and considerable potential applications of PPE-OBS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation